2017
DOI: 10.1111/1475-6773.12666
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Primary Care Pathways from Quality of Care to Outcomes and Satisfaction Using Structural Equation Modeling

Abstract: Objective. To study the relationships between the different domains of quality of primary health care for the evaluation of health system performance and for informing policy decision making. Data Sources. A total of 137 quality indicators collected from 7,607 English practices between 2011 and 2012. Study Design. Cross-sectional study at the practice level. Indicators were allocated to subdomains of processes of care ("quality assurance," "education and training," "medicine management," "access," "clinical ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…Previous studies [61][62][63] showed how structural equation modeling (SEM) could become an indispensable tool for managers, policymakers, and regulators in the healthcare sector. Our data came from indexes, as mentioned above, and were contained in a database; therefore, they were secondary data.…”
Section: Data and Samplementioning
confidence: 99%
“…Previous studies [61][62][63] showed how structural equation modeling (SEM) could become an indispensable tool for managers, policymakers, and regulators in the healthcare sector. Our data came from indexes, as mentioned above, and were contained in a database; therefore, they were secondary data.…”
Section: Data and Samplementioning
confidence: 99%
“…The latter could be due to patients’ necessary dependence on the health system [ 60 ]. Other research found a weak relationship between health condition and satisfaction [ 48 , 61 ]. However, in general, studies have found a negative relationship between mortality and patient satisfaction [ 62 , 63 , 64 ].…”
Section: Introductionmentioning
confidence: 99%
“…The importance of patient satisfaction research is that high satisfaction is associated with better clinical outcomes [ 47 ] and thus system quality. Some authors state that it may be a “cause–effect” relationship because satisfied patients may be more adherent to treatment and thus achieve better clinical outcomes [ 48 ]. For example, Chia confirmed that patient participation in the process of diagnosis and the degree of patient involvement in healthcare decision-making are associated with patient satisfaction [ 49 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it leaves out aspects of overall health that are not specific of a particular condition-specific set, such as those relevant to people with multimorbidity and polypharmacy [ 12 ]. These limitations undermine the appraisal of the value of services oriented towards health promotion and prevention, such as public health and primary care services [ 13 ]. Moreover, it is at odds with the renewed recognition of the essential role that these services play within health care systems and the support for primary care and public health functions as the core of integrated health services and one of the three pillars of the WHO’s primary health care approach [ 14 ].…”
Section: Introductionmentioning
confidence: 99%